Process Optimization and Antioxidant Activity Analysis of White Kidney Bean Polypeptides Prepared by Composite Strain Fermentation - Sinan LI; Meng WANG; Yu AN; Qing WANG; Kaiyuan XU; Jia WANG; Zhihui ZHANG; Xi WANG; Ying WANG; Lu ZHANG (Shipin gongye ke-ji)
In order to investigate the optimal process conditions and in vitro antioxidant activity of white kidney bean polypeptides (WKBPs) from complex strain fermentation, this study used Bacillus subtilis and Aspergillus oryzae as starter culture, and optimized the process of preparing WKBPs through single factor and response surface experiments. The in vitro antioxidant activity of WKBPs with different molecular weights was determined by ultrafiltration membrane separation, and the most active components were screened. The changes in antioxidant activity of WKBPs after gastrointestinal digestion were evaluated in combination with the simulated digestive system in vitro. The results showed that the yield of WKBPs was 63.47% under the conditions of fermentation time 48 h, temperature 37 ℃, inoculation amount 9% and the ratio of Aspergillus aspergillus and Bacillus subtilis 1:1. The molecular weight component WKBPs-4 （Mw<3 kDa） had good antioxidant activity after ultrafiltration. The concentration of WKBPs-4 was dose-dependent in the range of 0.2 to1.0 mg/mL, and the antioxidant capacity increased with the increase of WKBPs-4 concentration. The IC50 values of DPPH free radical clearance rate, ABTS+ free radical clearance rate, hydroxyl free radical clearance rate and Fe3+ reducing power were 0.47, 0.50, 0.46 and 0.66 mg/mL, respectively. After gastrointestinal digestion, WKBPs-4 still maintained high antioxidant activity. At the end point of intestinal digestion 240 min, the DPPH free radical clearance rate and ABTS+ free radical clearance rate were 84.29% and 77.34%, respectively. This study can provide theoretical basis and data support for high value utilization and deep processing of white kidney beans.